PENGARUH PENERAPAN PEMBELAJARAN AKTIF MODEL TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMA ADABIAH 2 PADANG TAHUN PELAJARAN 2013/2014 - Ahmad, Amri; Rahmi, Rahmi; Yunita, Alfi (STKIP PGRI Sumbar, 2014)
AbstractBackground of the research is student less comprehen of lesson concept, student less active in learning, and many student only cheat exercise their friendâs. Goals of research to describe studentâs activity by used active learning Team Assisted Individualization (TAI) model and to known what is Â students comprehension mathematical conceptâs by used that modelâs better than comprehension mathematical conceptâs by applying conventional teaching students in class XI IPA SMA Adabiah 2 Padang on 2013/2014. Type of research was experimental. Randomized Control Group Only Design. Instrument of the research was observation sheet and final test with indicator of comprehension mathematical concepts in the form of essay got reliability test 0,836. Based on data analysis both of class, one class samples have not normal distributions. data Analysis technique used non parametrik statistik part the help of Minitab, Mann-Whitney test got P-Value = 0,0000 with Î± =0,05, it means that the hypothesis was accepted.